2016
DOI: 10.1111/1462-2920.13388
|View full text |Cite
|
Sign up to set email alerts
|

Culture‐independent characterization of novel psychrophilic magnetotactic cocci from Antarctic marine sediments

Abstract: Magnetotactic bacteria (MTB) are a heterogeneous group of ubiquitous aquatic microorganisms capable of biomineralizing nano-sized, membrane-bound, magnetic iron-rich mineral particles called magnetosomes. MTB are found in chemically-stratified aquatic sediments and/or water columns with a wide range of salinities, moderate to high temperatures, and pH varying from neutral to strongly alkaline. MTB from very cold environments have not been investigated to any great degree and here we characterize MTB from the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 78 publications
0
20
0
Order By: Relevance
“…Magnetotactic cocci are one type of magnetotactic bacteria (MTB). Since the first description of MTB (Blakemore, 1975), many studies have shown that magnetotactic cocci are the most frequent morphotype among other MTB, both in freshwater (Moench and Konetzka, 1978; Spring et al, 1995; Flies et al, 2005a,b; Lin and Pan, 2009, 2010) and marine habitats (Spring et al, 1998; Abreu et al, 2012; Zhang et al, 2012; Du et al, 2017). However, only five representatives— Magnetococcus marinus MC-1 T (Frankel et al, 1997), Magnetofaba australis IT-1 (Morillo et al, 2014), “ Ca .…”
Section: Introductionmentioning
confidence: 99%
“…Magnetotactic cocci are one type of magnetotactic bacteria (MTB). Since the first description of MTB (Blakemore, 1975), many studies have shown that magnetotactic cocci are the most frequent morphotype among other MTB, both in freshwater (Moench and Konetzka, 1978; Spring et al, 1995; Flies et al, 2005a,b; Lin and Pan, 2009, 2010) and marine habitats (Spring et al, 1998; Abreu et al, 2012; Zhang et al, 2012; Du et al, 2017). However, only five representatives— Magnetococcus marinus MC-1 T (Frankel et al, 1997), Magnetofaba australis IT-1 (Morillo et al, 2014), “ Ca .…”
Section: Introductionmentioning
confidence: 99%
“…These known cultured and uncultured MTB have been assigned to the Alpha -, Gamma -, and Delta-proteobacteria classes of the Proteobacteria phylum (Lefèvre and Bazylinski, 2013), the Nitrospirae phylum (Spring et al, 1993), and even the “ Candidatus Omnitrophica” phylum (Kolinko et al, 2012). Despite the morphological and phylogenetic diversity of MTB, the most commonly observed types present in natural environments are coccoid-to-ovoid cells, the so-called magnetococci (Moench and Konetzka, 1978; Spring et al, 1992, 1995; Thornhill et al, 1995; Cox et al, 2002; Flies et al, 2005; Pan et al, 2008, 2009; Lin and Pan, 2009; Zhang et al, 2012; Chen et al, 2015; Abreu et al, 2016). Previous 16S rDNA phylogenetic analyses have shown that magnetococci are also highly diverse.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we performed a systematic investigation of the bacterial diversity and community structure in sediments collected from 14 stations on a seamount located in the tropical western Pacific Ocean; additionally, this cruise marks the first time this seamount has been surveyed. We focused on the occurrence of seamount magnetotactic bacteria (MTB) that are widely distributed in freshwater and marine ecosystems 12 16 . MTB are a morphologically, phylogenetically, and physiologically diverse group of bacteria that produce single-domain magnetite (Fe 3 O 4 ) or greigite (Fe 3 S 4 ) crystals in intracellular organelles called magnetosomes.…”
Section: Introductionmentioning
confidence: 99%